USED PAPER KEYCHANGING CRAFTS REVIEWING FROM MATERIAL, SHAPE, AND FUNCTION - Tifani Weka Iwanda; Adek Cerah Kurnia Azis (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2022)
Keychain crafts not only function as hooks or decorative objects but have been used as promotional tools for various ethnic groups, ranging from the shape of traditional clothing motifs to a variety of traditional foods in Sumatra, the materials used in each craft making will support the craft created and function the use of these crafts, where the key chain craft that is created is not enough as a functional work, it is not enough to only fulfill the functional aspect but requires a touch of beauty to increase its quality and economic value.Keywords: Online Learning; Impact; Effort; Image Shapes.KERAJINAN GANTUNGAN KUNCI KERTAS BEKAS DITINJAU DARI BAHAN, BENTUK DAN FUNGSI AbstrakKerajinan gantungan kunci tidak hanya berfungsi sebagai pengail maupun benda hias saja, namun telah dijadikan sebagai alat promosi berbagai suku,  mulai dari bentuk motif pakaian adat maupun ragam makanan khas adat di Sumatera, bahan yang digunakan pada setiap pembuatan  kerajinan akan mendukung kerajinan yang tercipta dan fungsi pakai dari kerajinan tersebut, dimana kerajinan gantungan kunci yang diciptakan tidak cukup sebagai karya fungsional tidak cukup hanya memenuhi aspek fungsi saja melainkan memerlukan sentuhan keindahan untuk meningkatkan kualitas dan nilai ekonomisnya.Kata kunci : Pembelajaran Daring; Dampak; Upaya; Gambar Bentuk.